2019
DOI: 10.1186/s13104-019-4137-z
|View full text |Cite
|
Sign up to set email alerts
|

On the length, weight and GC content of the human genome

Abstract: Objective Basic parameters commonly used to describe genomes including length, weight and relative guanine-cytosine (GC) content are widely cited in absence of a primary source. By using updated data and original software we determined these values to the best of our knowledge as standard reference for the whole human nuclear genome, for each chromosome and for mitochondrial DNA. We also devised a method to calculate the relative GC content in the whole messenger RNA sequence set and in transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 51 publications
8
122
2
Order By: Relevance
“…This difference is why DNA with low GC-content is less stable than DNA with high GC-content. Among all 22 autosomes, the average of GC-content is 41.62% [19,20]. 27.27%, 6/22 of autosomes have GC contents below 40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is why DNA with low GC-content is less stable than DNA with high GC-content. Among all 22 autosomes, the average of GC-content is 41.62% [19,20]. 27.27%, 6/22 of autosomes have GC contents below 40%.…”
Section: Resultsmentioning
confidence: 99%
“…Due to small sample size, we cannot robustly ascertain whether a low GC-content sequence would be more vulnerable to DNA breakpoints than a high GC-content sequence. However, utilizing GC content and reciprocal sub-chromosomal arm gain-loss complementary as a reference may prove a more e cient tool in distinguishing real DNA segments from NGS data noise generated from a sample of DNA in SCM [19,32] .…”
Section: Resultsmentioning
confidence: 99%
“…This pronounced difference in stiffness may be explained in terms of molecular structures of chromosomal DNA and mRNA molecules within the nucleus, given that Henderson et al (26) observed that regions of low DNA have a high RNA concentration. DNA molecules in eukaryotic cells are thin polymers of length 3-6 cm (36), that must be compacted to fit in the finite volume of a cell nucleus (typically of diameter is 5-10 μm). Thus, the DNA molecule is envisioned as an extremely long thin string of moderate elasticity that is bent into the configurations required for packaging, and, when associated with histones, this compacted complex forms chromatin (37).…”
Section: Discussionmentioning
confidence: 99%
“…Monosomies (possessing only one chromosome of a pair) are basically deleterious due to the level of gene expression being insufficient for cell survival; most such cases, except for monosomy X, are thus embryonically lethal [13]. In contrast, live births occur for trisomies of chromosomes 13, 18, 21, X, and Y, owing to the smaller number of genes encoding proteins located on these chromosomes in comparison to the other autosomal chromosomes [14][15][16][17][18]. However, trisomy 13 and trisomy 18 have severe phenotypic consequences, which are rarely compatible with long-term survival [19][20][21][22].…”
Section: Human Genetic Aneuploidy Disordersmentioning
confidence: 99%